International Collaborative Research: Responsive Partnership, Value and the Missing Link in Indonesia - Wahyono, Sri (KnE Social Sciences, 2022)
Academic research is increasingly international. Collaboration across cultural and geographic boundaries increases efficiency and speeds up the new discoveries of science and technology by combining skills. However, the management of international research collaborations is far from simple. The equity and impact of a partnership must be supported by strong management and support systems. The success in organizing a research partnership is substantially dependent on the supporting management system. Researchers who search for partnerships, obtain funding and are responsive partners should be supported by the State. The Government should assist these partnerships, not only regulate and control them. Providing support e.g., matching funds, assisting capacity building for researchers, developing infrastructure and institutional development capacity, and providing research management training can boost the achievement of ideal international research collaborations with high impacts and benefits for all parties. This research examined the conditions and obstacles for international research collaborations in Indonesia of various research and development institutions and universities with their international research partners. Qualitative methods were used. The study used a range of research permit and publication indicators to measure the benefits obtained from international partnerships. It was found that one of the most successful international research partnerships in Indonesia, which has existed for 20 years, has been able to achieve optimal benefit-sharing such as co-authorship, co-supervision, mobility of students and staff, and capacity building of the Indonesian scientists and institutions. Keywords: international research collaboration, permit, research management, supporting system